C Pengaruh Ukuran Perusahaan, Struktur Aset, dan Profitabilitas terhadap Struktur Modal - Rahardian Suryo Utomo Suryo; Ika Rosyada Fitriati (Universitas Sains dan Teknologi Komputer, 2022)
Capital Structure discusses how the company provides capital asstes, either with long-term debt or capital from investors. This research aims to examine and analyze company size, asset structure, and profitability on capital structure in automotive retail and automotive equipment companies listed on the BEI 2011-2020. The data used the company’s financial statements that are sampled. The sampling method used purposive sampling technique and obtained 90 samples. The results of analysis showed company size had a significant positive on capital structure, asset structure had an insignificant negative on capital structure, and profitability was proxied using Debt to Equity Ratio (DER) has no effect on the capital structure.